2009
DOI: 10.1103/physrevb.80.144417
|View full text |Cite|
|
Sign up to set email alerts
|

Phase diagram of an anisotropic frustrated ferromagnetic spin-12chain in a magnetic field: A density matrix renormalization group study

Abstract: We study the phase diagram of a frustrated spin-1 2 ferromagnetic chain with anisotropic exchange interactions in an external magnetic field using the density matrix renormalization group method. We show that an easy-axis anisotropy enhances the tendency toward multimagnon bound states while an easy-plane anisotropy favors chirally ordered phases. In particular, a moderate easy-plane anisotropy gives rise to a quantum phase transition at intermediate magnetization. We argue that this transition is related to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…In a very recent density-matrix renormalization group study the anisotropic model at finite magnetization was investigated. 15 A dimer phase was not found to be stable, instead it was shown that for most parameters a chiral phase or a spin liquid phase (SDW 2 phase) occur.…”
Section: The Anisotropic Casementioning
confidence: 99%
“…In a very recent density-matrix renormalization group study the anisotropic model at finite magnetization was investigated. 15 A dimer phase was not found to be stable, instead it was shown that for most parameters a chiral phase or a spin liquid phase (SDW 2 phase) occur.…”
Section: The Anisotropic Casementioning
confidence: 99%
“…[16][17][18][19][20] Despite its simplicity, the 1D J 1 -J 2 Heisenberg model has been shown to exhibit various unconventional phases under magnetic field ͑as we summarize below͒. [21][22][23][24] In this paper we aim to clarify the nature of the phases in the ground-state phase diagram of the 1D spin-1 2 J 1 -J 2 Heisenberg model under magnetic field, when both nearest-and next-nearest-neighbor exchange couplings are antiferromagnetic ͑AF͒. To this end, we study in detail spin correlations in each phase using the numerical density-matrix renormalization-group ͑DMRG͒ method as well as lowenergy effective theory based on bosonization.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] By comparing the measured thermomagnetic properties with theoretical calculations, the role of interchain interactions J i , anisotropy ∆, and other sub-leading interactions can be inferred. [11][12][13]10] Spin-ladders can be thought of as an intermediate system between purely 1D spin-chains and 2D spin-sheets. [14,15] The correlated physics is more intricate than for spin-chains without the full complexity of a 2D magnetic lattice.…”
Section: Introductionmentioning
confidence: 99%